"Honey moon" meningitis. Issue 11 (21st October 2005) - Agouridakis, P; Ioannidou, E; Dalezios, M; Panagopoulou, V; Drandakis, P
Abstract : Streptococcus agalactiae is a rare cause of meningitis in healthy non-pregnant adults. A case of S. agalactiae meningitis is reported in a previously healthy young woman following sexual intercourse for the first time. The vaginal flora was the verified source of infection.